1998
DOI: 10.1177/109019819802500306
|View full text |Cite
|
Sign up to set email alerts
|

Sociopsychological Correlates of Motivation to Quit Smoking Among Low-SES African American Women

Abstract: This article examines correlates of desire and plans to quit smoking among 248 young, low-socioeconomic status African American women, using variables derived from the health belief model (HBM) and the theory of reasoned action. Consistent with these theoretical models, stronger concern about the effect of smoking on one's health and having close others who want the smoker to quit increased motivation to quit smoking. However, motivation was not associated with specific HBM components regarding lung cancer. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Individuals with initially high levels of perceived susceptibility exhibited lower levels of consumption (Mullens, Hersey and Iverson, 1987). Perceived susceptibility was found to be significantly related to smokers' desire, readiness or intentions to quit (Manfredi, Lacey, Warnecke and Petraitis, 1998;Norman et al, 1999;Tessaro et al, 1997). Strecher, Becker, Kirscht, Eraker and Graham-Tomasi (1985) combined susceptibility to smoking illness from continuing smoking with susceptibility to illness from quitting smoking and found that this measure was strongly associated with a desire to quit smoking.…”
Section: The Health Beliefs Model (Hbm)mentioning
confidence: 91%
“…Individuals with initially high levels of perceived susceptibility exhibited lower levels of consumption (Mullens, Hersey and Iverson, 1987). Perceived susceptibility was found to be significantly related to smokers' desire, readiness or intentions to quit (Manfredi, Lacey, Warnecke and Petraitis, 1998;Norman et al, 1999;Tessaro et al, 1997). Strecher, Becker, Kirscht, Eraker and Graham-Tomasi (1985) combined susceptibility to smoking illness from continuing smoking with susceptibility to illness from quitting smoking and found that this measure was strongly associated with a desire to quit smoking.…”
Section: The Health Beliefs Model (Hbm)mentioning
confidence: 91%
“…Similar to findings regarding risk perceptions, data illustrate the association of worry with several healthprotective behaviors. For example, studies show that worry predicts uptake of mammography screening [28] and smokers' plans and desire to quit [29]. Moreover, Lipkus and Prokhorov [30] found that smoking-related worry, but not perceived risk, was associated with a stronger desire to quit smoking.…”
Section: Risk Worry and Health Behaviorsmentioning
confidence: 98%
“…Socioeconomic status, most often assessed by the proxy variables of education and income, is a powerful structural correlate of smoking initiation, persistence, and cessation (e.g., Gilman, Abrams, & Buka, 2003;Harrell, Bangdiwala, Deng, Webb, & Bradley, 1998;Manfredi, Lacey, Warnecke, & Petraitis, 1998;Stronks, van de Mheen, Looman, & Mackenbach, 1997). Smith and Fiore (1999) argued that "among sociodemographic predictors of differences in rates of current smoking, educational attainment has replaced sex as the most predictive characteristic" (p. 439).…”
Section: Social Structure and Smokingmentioning
confidence: 98%